Performance of ASN (Government Employee) in Implementation of the Work from Home Policy in the Regional Secretariat of Bogor Regency - Amelia, Nita; Maarif, syamsul; Hubies, Aida Vitalaya (Jurnal Manajemen, 2021)
Working from home (WFH) is a new work pattern applied by organizations and government agencies. During the COVID-19 pandemic, if it becomes an alternative for companies and agencies to keep working, performance can still be achieved. This study aims to see the effect of readiness on performance, readiness to change on readiness for acceptance of technology, acceptance of the technology on performance during work from home of governance employee in the Regional Secretariat of Bogor Regency. This study involved 136 respondents, with the sampling method used in this study is non-probability sampling. The sampling technique used is Voluntary Sampling. The Structural Equation Model-PLS analysis results showed that readiness to change had a significant effect on performance, readiness to change had an effect on readiness for technology acceptance, readiness for technology acceptance had a significant effect on performance, and there was no difference between the performance of men and women at work from home.